2019
DOI: 10.3390/molecules25010021
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of 1,2-Aminoalcohols with Neoisopulegol-Based Octahydrobenzofuran Core

Abstract: A library of 1,2-aminoalcohol derivatives with a neoisopulegol-based octahydrobenzofuran core was developed and applied as chiral catalysts in the addition of diethylzinc to benzaldehyde. The allylic chlorination of (+)-neoisopulegol, derived from natural (-)-isopulegol followed by cyclization, gave the key methyleneoctahydrobenzofuran intermediate. The stereoselective epoxidation of the key intermediate and subsequent oxirane ring opening with primary amines afforded the required 1,2-aminoalcohols. The ring c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…[89] 1,2-Aminoalcohols containing additional moieties between the 1,2-aminoalcohol unit [84] and the octabenzohydrofuran core were synthesized by Bamou et al in 2019 starting from (+)-neoisopulegol 3. [90] Allylic chlorination of (+)-3 followed by cyclisation produced (À )-methylenetetrahydrofuran 147 b. [91]…”
Section: 2-aminoalcohols With Neoisopulegol-based Octahydrobenzofuran Corementioning
confidence: 99%
“…[89] 1,2-Aminoalcohols containing additional moieties between the 1,2-aminoalcohol unit [84] and the octabenzohydrofuran core were synthesized by Bamou et al in 2019 starting from (+)-neoisopulegol 3. [90] Allylic chlorination of (+)-3 followed by cyclisation produced (À )-methylenetetrahydrofuran 147 b. [91]…”
Section: 2-aminoalcohols With Neoisopulegol-based Octahydrobenzofuran Corementioning
confidence: 99%
“…[36,37] βamino alcohols are produced from the asymmetric ring opening reaction of epoxides with amines [38][39][40] and have recently gained popularity in organic synthesis and pharmaceutical development. [41][42][43][44][45] The purpose of this work is to generate mesoporosity in SAPO-34 and SAPO-5 catalysts by post-synthetic acid and alkali treatment and use the modified materials in epoxide ring opening reaction to check the effectiveness of the materials. To the best of our knowledge, no thorough study on using both acid and alkali treated SAPO-34 and SAPO-5 materials and their catalytic application on epoxide ring opening reaction is available.…”
Section: Introductionmentioning
confidence: 99%
“…The microbial biofilm-forming ability is one of the major aspects of the emerging issue of antibiotic resistance, which makes them tolerant to antibiotics and host defence systems and other external stresses, thus contributing to persistent chronic infections (5). Several studies confirmed the high efficiency of aminopropanol derivatives as potential antibacterial and antifungal agents, which actually drew our interest to compounds of this group (6,7,8).…”
Section: Introductionmentioning
confidence: 99%